2000
DOI: 10.1074/jbc.m910281199
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes Reduce Extracellular Ascorbate Free Radicals Using Intracellular Ascorbate as an Electron Donor

Abstract: Ascorbate is readily oxidized in aqueous solution by ascorbate oxidase. Ascorbate radicals are formed, which disproportionate to ascorbate and dehydroascorbic acid. Addition of erythrocytes with increasing intracellular ascorbate concentrations decreased the oxidation of ascorbate in a concentration-dependent manner. Concurrently, it was found, utilizing electron spin resonance spectroscopy, that extracellular ascorbate radical levels were decreased. Control experiments showed that these results could not be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 45 publications
1
46
0
3
Order By: Relevance
“…The GSH concentration was routinely tested with DTNB as indicated above for cysteine quantification, and the concentration of ascorbate was monitored with measurements of the absorbance at 265 nm, using an extinction coefficient of 14 500 M -1 ‚cm -1 (46).…”
Section: Measurement Of Peroxynitrite Produced During Sin-1 Decomposimentioning
confidence: 99%
“…The GSH concentration was routinely tested with DTNB as indicated above for cysteine quantification, and the concentration of ascorbate was monitored with measurements of the absorbance at 265 nm, using an extinction coefficient of 14 500 M -1 ‚cm -1 (46).…”
Section: Measurement Of Peroxynitrite Produced During Sin-1 Decomposimentioning
confidence: 99%
“…Il permet par ailleurs une polymérisation complète des radicaux libres de l'adhésif et la formation d'une couche hybride étanche et uniforme à l'interface résine/dent [34,35,36]. L'ascorbate de sodium est préféré à l'acide ascorbique pour éviter l'effet de double mordançage à l'A.…”
Section: Les Antioxydants Non Enzymatiquesunclassified
“…Unlike its effect on AA: ferricyanide oxidoreductase activity, pCMBS does not affect the preservation of extracellular AA. Van Duijn et al (28) found that low NADH concentrations resulted in higher rates of AA oxidation to AFR, while the opposite was found for high NADH concentrations, indicating that NADH is a necessary requirement for AA regeneration from AFR. This group speculated on the functional components of the electron transport system claiming that an a-TH shuttle was an unlikely candidate given the redox potential ( Table 2) and electrogenic nature of the transport.…”
Section: Redox Half Reaction E8 (Mv)mentioning
confidence: 99%
“…The more hyperpolarized the membrane, the faster the AFR reduction (17). Enhancement of AFR reduction can also be achieved by increasing the intracellular AA concentration (28). The reductase activity is inhibited by NEM, which brings about a loss of available GSH, presumably the basis of decreased intracellular AA recycling (27).…”
Section: Redox Half Reaction E8 (Mv)mentioning
confidence: 99%
See 1 more Smart Citation